2013
DOI: 10.1371/journal.pone.0060225
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity of Pseudomonas aeruginosa Populations in a Cystic Fibrosis Patient

Abstract: The opportunistic pathogen Pseudomonas aeruginosa chronically infects the lower airways of patients with cystic fibrosis. Throughout the course of infection this organism undergoes adaptations that contribute to its long-term persistence in the airways. While P. aeruginosa diversity has been documented, it is less clear to what extent within-patient diversity contributes to the overall population structure as most studies have been limited to the analysis of only a few isolates per patient per time point. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
192
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(207 citation statements)
references
References 58 publications
(52 reference statements)
11
192
2
2
Order By: Relevance
“…These characteristics represent potential possibilities for future studies. Also, recent analyses showed that traditional culture methods (i.e., isolating a small number of morphologically different bacterial colonies from each culture) frequently underrepresent the P. aeruginosa diversity in individual samples of CF respiratory secretions during chronic infection with respect to several phenotypes (44)(45)(46)(47); therefore, even the large isolate collection in this study likely undersampled the phenotypic diversity of P. aeruginosa in each subject. Similarly, it is possible that sputum and OP specimens are not sufficiently sensitive to reflect the earliest stages of infection, whether of the lower or upper airways (48,49), potentially explaining the observed high frequency in our "early" isolates of phenotypes commonly associated with adaptation.…”
Section: Discussionmentioning
confidence: 84%
“…These characteristics represent potential possibilities for future studies. Also, recent analyses showed that traditional culture methods (i.e., isolating a small number of morphologically different bacterial colonies from each culture) frequently underrepresent the P. aeruginosa diversity in individual samples of CF respiratory secretions during chronic infection with respect to several phenotypes (44)(45)(46)(47); therefore, even the large isolate collection in this study likely undersampled the phenotypic diversity of P. aeruginosa in each subject. Similarly, it is possible that sputum and OP specimens are not sufficiently sensitive to reflect the earliest stages of infection, whether of the lower or upper airways (48,49), potentially explaining the observed high frequency in our "early" isolates of phenotypes commonly associated with adaptation.…”
Section: Discussionmentioning
confidence: 84%
“…However, once PES was identified during serial assessments of patients with displacement events, unique strains were no longer observed. Furthermore, in a small sample of patients infected with PES for which morphotypic diversity was explored in great depth, coinfections were not observed (52). The identification of a high degree of concordance in infecting strains at FE and RE does not strictly rule out the possibility of a transient infection with other strains during time points not assessed.…”
Section: Figmentioning
confidence: 92%
“…The observed increased incidence of aminoglycoside and fluoroquinolone nonsusceptibility in PES during our study may indicate an increased treatment requirement and treatment burden in those infected with PES. PES has been demonstrated to be capable of tremendous within-patient phenotypic diversity, as measured by colony morphology, motility, protease production, auxotrophy, siderophore production, antibiotic resistance, quorum sensing, and growth patterns, similar to the within-patient heterogeneity of LES (51,52).…”
Section: Figmentioning
confidence: 99%
“…However, CF P. aeruginosa populations were shown to be highly diverse. Indeed, in the same sputum sample, colonies that were assayed for a range of phenotypic traits, known to be altered during evolutionary adaptation, showed significant within-specimen diversity (4)(5)(6)(7). The resulting coexistence of variant lineages in the respiratory tract of CF patients suggested that they arose from diverse selection pressures in the lung and then developed distinct evolutionary pathways (5,6,8).…”
mentioning
confidence: 99%